2017
DOI: 10.25115/psye.v9i3.1024
|View full text |Cite
|
Sign up to set email alerts
|

Expert’s opinion of a home-based exercise program for shoulder pain prevention: application in wheelchair basketball players.

Abstract: The aim of the study was to assess the structure and content validity of a home-based exercise program, as an instrument to prevent of shoulder pain (SP) in wheelchair basketball players. The proposed program was designed considering previous studies but to be applied in this specific population and; it was composed by exercises based on active mobility (4 exercises), strengthening (5 exercises) and stretching (5 exercises) of the shoulder joint. An ad hoc questionnaire was administered to a convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…In contrast with previous research [23,31,51], this study shows that a SHEP seems appropriate to prevent the development of SP and re-injury. In accordance with this, a study by García-Gómez et al [37] reported evidence for the adequate structure and content validity of a SHEP according to expert opinions. The exercise program included special attention to front chest musculature and the back of the shoulder joint, which is often tight when the wheelchair user has a limited inward rotation of the shoulder [52].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In contrast with previous research [23,31,51], this study shows that a SHEP seems appropriate to prevent the development of SP and re-injury. In accordance with this, a study by García-Gómez et al [37] reported evidence for the adequate structure and content validity of a SHEP according to expert opinions. The exercise program included special attention to front chest musculature and the back of the shoulder joint, which is often tight when the wheelchair user has a limited inward rotation of the shoulder [52].…”
Section: Discussionmentioning
confidence: 58%
“…The WB players allocated to the intervention group followed a detailed protocol including strengthening and stretching exercises in the upper extremities [26,27,28,29,30], along with general recommendations. In order to assure the quality and consistency of the SHEP, a qualitative analysis was developed based on the expert opinions of health and sport professionals, including a rehabilitation physician, a sport physician, physiotherapists and coaches [37].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second part of the program included specific Mulligan manual techniques, individually selected according to the symptoms of each participant. To assure the quality and consistency of the individual physiotherapy program, a qualitative analysis was developed based on the expert opinions of health and sports professionals, including a sports physician, physiotherapists and coaches (García-Gómez et al 2017). The second part of the individual programs were individually selected by the physiotherapy team of 4 people.…”
Section: Interventionmentioning
confidence: 99%
“…About 80% of wheelchair basketball players reported shoulder pain-related activities of daily living (ADL) or sports activities Pérez-Tejero et al, 2006). Overhead movements involved in many daily living activities and also many sports activities with even higher load may promote shoulder pain García-Gómez et al, 2017;Curtis et al, 1985).…”
Section: Introductionmentioning
confidence: 99%